Maternal Separation Stress Affects Voluntary Ethanol Intake in a Sex Dependent Manner - Bertagna, Natalia Bonetti; Favoretto, Cristiane Aparecida; Rodolpho, Ben Tagami; Palombo, Paola; Yokoyama, Thais Suemi; Righi, Thamires; Loss, Cássio Morais; Leão, Rodrigo Molini; Miguel, Tarciso Tadeu; Cruz, Fábio Cardoso (Frontiers in Physiology, 2021)
Maternal separation (MS) stress is a predictive animal model for evaluating the effects of early stress exposure on alcohol use disorders. The extended amygdala is a complex circuit involved in both stress- and ethanol-related responses. We hypothesized that MS stress may increase ethanol consumption in adulthood, as well as augmented neuronal activity in extended amygdala, in a sex-dependent manner. We aimed to investigate the influence of MS stress on the ethanol consumption of male and female mice, and the involvement of extended amygdala sub-nuclei. The C57BL/6J pups were subjected to 180 min of MS, from postnatal day (PND) 1 to 14. The control group was left undisturbed. On PND 45, mice (n=28) in their home cages were exposed to a bottle containing 20% ethanol (w/v) for 4h during the dark period of the light-dark cycle, for 3 weeks. Afterwards, mice underwent ethanol self-administration training in operant chambers under fixed ratio (FR) schedule. Then, subjects were tested under 2h sessions of a progressive-ratio schedule of reinforcement (the last ratio achieved was considered the breaking point), and at the end, a 4h session of FR schedule (binge-intake). An immunohistochemistry assay for Fos protein was performed in Nucleus Accumbens (NAcc), Bed Nucleus of Stria Terminalis (BNST), and Amygdala (AMY). Our results showed that in the third week of training, the female maternal separation group consumed more ethanol than the respective control group. The MS group presented increased breakpoint parameters. Female control group and male MS group are more resistant to bitter quinine taste. Increased Fos-immunoreactive neurons were observed in the central nucleus of AMY, but not in NAcc nor BNST in male maternal-separated mice. Maternal separation stress may influence ethanol intake in adulthood, and it is dependent on the sex and reinforcement protocol.